Elastic-plastic stress analysis of a thermoplastic composite disc under a steady state temperature distribution - Sayman, Onur; Duranay, Mehmet; Gur, Mustafa; Kocak, Saim (Walter de Gruyter Gmbh, 2006)
In the present study, an elastic-plastic stress analysis is carried out on a steel fiber reinforced thermoplastic composite disc under a temperature distribution of steady state case. An analytical formulation is obtained and then the solution is performed numerically. The Tsai-Hill theory is used as yield criterion in the solution. The magnitude of the tangential stress component was found to be higher than that of the radial stress component. The obtained results also revealed that the tangential stress is compressive and tensile at the inner and outer disc radii, respectively. A solution was also obtained by FEM using the ANSYS program. These two solutions give close results.
Keywords: Residual-Stresses; Variable Thickness; Plates